Negotiating Cooperation under Uncertainty: Communication in Noisy, Indefinitely Repeated Interactions - Fabian Dvorak; Sebastian Fehrler (Institute of Labor Economics (IZA), 2018)
Case studies of cartels and recent theory suggest that repeated communication is key for stable cooperation in environments where signals about others' actions are noisy. However, empirically the exact role of communication is not well understood. We study cooperation under different monitoring and communication structures in the laboratory. Under all monitoring structures - perfect, imperfect public, and imperfect private - communication boosts efficiency. However, under imperfect monitoring, where actions can only be observed with noise, cooperation is stable only when subjects can communicate before every round of the game. Beyond improving coordination, communication increases efficiency by making subjects' play more lenient and forgiving. We further find clear evidence for the exchange of private information - the central role ascribed to communication in recent theoretical contributions.
Keywords: C72; C73; C92; D83; 330; infinitely repeated games; monitoring; communication; cooperation; strategic uncertainty; prisoner's dilemma